Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan PT Bambang Djaja Surabaya - Raihananda, Wildan Jordiansyah; Irawati, Anugrahini (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this study was to determine the Influence of Organizational Culture and Organizational Commitment, both simultaneously and partially on the performance of employees at PT. Bambang Djaja. This research was conducted using a quantitative approach. The analytical method used in this research is multiple linear analysis. The data used primary and secondary obtained a total sample of 80 respondent. The hypothesis testing used is multiple linear analysis. The limitation of this research is that the assessment was conducted only focusing on the influence of several factors of organizational commitment on employee performance. The conclusions in this study are only based on the acquisition of data analysis, is is necessary to develop further research to examine the influence of other factors that have not been studied regarding organizational culture and organizational commitment on employee performance with different research methods, a wider sample, and the use research instrument different and morecemplete.